Designing for Slowness, Anticipation and Re-visitation: A Long Term Field Study of the Photobox - Odom, William T.; Sellen, Abigail; Banks, Richard; Kirk, David; Regan, Tim; Selby, Mark; Forlizzi, Jodi L.; Zimmerman, John (Proceedings of the 32Nd Annual ACM Conference on Human Factors in Computing Systems, 2014)
We describe the design, implementation and deployment of Photobox, a domestic technology that prints four or five randomly selected photos from the owner's Flickr collection at random intervals each month. We deployed Photobox in three homes for fourteen months, to explore how the slow pace at which it operates could support experiences of anticipation and re-visitation of the past. Findings reveal changes in attitude toward the device, from frustration to eventual acceptance. Participants drew on the photos to reflect on past life events and reactions indicated a renewed interest for their Flickr collection. Photobox also provoked reflection on technology in and around the home. These findings suggest several opportunities, such as designing for anticipation, better supporting reflection on the past, and, more generally, expanding the slow technology research program within the HCI community.